SDL '99, the next millennium : proceedings of the ninth SDL Forum, Montréal, Québec, Canada, 21-25 June, 1999 /: proceedings of the ninth SDL Forum, Montréal, Québec, Canada, 21-25 June, 1999. (1999) - Unknown
No abstract available